2002
DOI: 10.1097/00005768-200203000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Central and peripheral cardiovascular adaptations during a maximal cycle exercise in boys and men

Abstract: The patterns of stroke volume, as well as its underlying mechanisms, were not age-related during an upright maximal exercise test. However, other studies are required to understand further the effect of pubertal status on the peripheral cardiovascular system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 29 publications
4
22
0
1
Order By: Relevance
“…Equation 8 suggests, however, that if the max-to-rest ratios of SV and (CaO 2 )C" vO 2 ) were approximately constant across individuals, _ V O 2max per kg BM may be estimated by experimentally determining the HR max -to-HR rest ratio, and multiplying this ratio with these constants and 3.4 mlAEmin )1 AEkg )1 . Nottin et al (2002) and Chapman et al (1960) reported the average SV max AESV rest )1 to be 1.28 and 1.29, respectively, in men, when measured in the supine position. Thus, according to the studies mentioned it appears that SV max AESV rest )1 may be replaced by a dimensionless value of approximately 1.3.…”
Section: Resultsmentioning
confidence: 99%
“…Equation 8 suggests, however, that if the max-to-rest ratios of SV and (CaO 2 )C" vO 2 ) were approximately constant across individuals, _ V O 2max per kg BM may be estimated by experimentally determining the HR max -to-HR rest ratio, and multiplying this ratio with these constants and 3.4 mlAEmin )1 AEkg )1 . Nottin et al (2002) and Chapman et al (1960) reported the average SV max AESV rest )1 to be 1.28 and 1.29, respectively, in men, when measured in the supine position. Thus, according to the studies mentioned it appears that SV max AESV rest )1 may be replaced by a dimensionless value of approximately 1.3.…”
Section: Resultsmentioning
confidence: 99%
“…The stroke volume, i.e., the quantity of blood ejected from the left ventricle during a systole, shows curvilinear kinetics in children during progressive physical exercise 3,9,17,18 , which is the same behavior seen in adults 19,20 . In an important study using Doppler and bidimensional echocardiography, Rowland et al 17 , attributed this curvilinear profile (plateau) to several mechanisms.…”
Section: Stroke Volumementioning
confidence: 73%
“…According to the authors, 18 the main finding of this investigation was the fact that children and adults use similar mechanisms for SV adaptation in face of progressive physical exercise. In spite of similar SV kinetics between children and adults, the pediatric population shows an attenuated inotropic response, and consequently, lower resting and exercise (submaximal or maximal) values for SV in comparison to those observed in their adult congeners 2,3,8,9 ( Fig.…”
Section: Stroke Volumementioning
confidence: 88%
See 1 more Smart Citation
“…This increase may be related to adaptations in the cardiovascular control sites such as hypothalamus, nucleus tractus solitarius (NTS), and rostral-ventrolateral medulla (RVLM) and these adaptations seem to occur by means of both neural remodeling and endogens factors such as nitric oxide [33][34][35][36]. In this sense, these central adaptations would improve the regulation of sympathetic and parasympathetic autonomic influences on the heart; however we cannot exclude the fact that physical exercise can also promote intrinsic cardiac adaptations, thus contributing to a better autonomic influence on HRV [35][36][37].…”
Section: Parametersmentioning
confidence: 99%